1996
DOI: 10.1093/bja/76.6.847
|View full text |Cite
|
Sign up to set email alerts
|

Halothane and potassium channels in airway smooth muscle

Abstract: Earlier studies have suggested that halothane may relax smooth muscle in part by opening adenosine triphosphate-sensitive potassium (KATP) channels. We tested this hypothesis in vitro by examining the interaction of halothane with glibenclamide, a KATP channel blocker, and YM934, a KATP channel opener, in strips of canine tracheal smooth muscles mounted in an organ bath system. To examine the specificity of any effects of halothane on the KATP channel, we assessed the interaction of halothane with tetraethylam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
6
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
3
6
0
Order By: Relevance
“…This is consistent with several studies that suggest that activation of K ATP channels could play a prominent role in volatile anaesthesia-induced relaxation of peripheral airways [24], coronary vessels [25], and cerebral vessels [28]. In contrast, FUKUSHIMA et al [14] found that glibenclamide pretreatment did not modify the concentrationdependent relaxation produced by halothane on canine tracheal strips incubated with indomethacin and precontracted with acetylcholine. Differences between contracting stimuli, tracheal versus distal airway smooth muscle, and/or between species may account for these conflicting results.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This is consistent with several studies that suggest that activation of K ATP channels could play a prominent role in volatile anaesthesia-induced relaxation of peripheral airways [24], coronary vessels [25], and cerebral vessels [28]. In contrast, FUKUSHIMA et al [14] found that glibenclamide pretreatment did not modify the concentrationdependent relaxation produced by halothane on canine tracheal strips incubated with indomethacin and precontracted with acetylcholine. Differences between contracting stimuli, tracheal versus distal airway smooth muscle, and/or between species may account for these conflicting results.…”
Section: Discussionsupporting
confidence: 91%
“…The concentration-dependent relaxant effect of volatile anaesthetics on human airway smooth muscle within clinical useful concentrations (0.66-2.0 MAC) is in accordance with most of the studies performed on animal airway smooth muscle [11,13,14,[16][17][18][19]. However, KORENAGA et al [8] found that dog tracheal airway smooth muscle contraction was significantly reduced by 1.2 MAC of halothane only when contraction was indirectly evoked by nerve stimulation.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations